Geophysical monitoring of large-scale levee overflow experiments with electrical resistivity tomography - Tsimopoulou , Vana; Karaoulis, Marios; Nieboer, Roeland; Ahlrichs, Edvard; Koelewijn, André; Kieftenburg, Annette (Journal of Coastal and Hydraulic Structures, 2025)
In the Interreg-funded Polder2C’s project, large-scale overflow experiments were conducted from 2020 to 2022 on levee slopes along the Scheldt River in Belgium and the Netherlands. These tests assessed surface erosion resistance under varied conditions, including levee sections containing animal-induced damages. Electrical Resistivity Tomography (ERT) was employed as a non-invasive monitoring tool to observe subsurface changes, particularly those linked to erosion-prone animal burrows. A unique system configuration enabled detailed imaging of the levee’s internal dynamics during overflow testing. Post-processed ERT data effectively captured subsurface changes during these events, including water infiltration into existing burrows, cavity formation and collapse, and the interconnection of subsurface voids. The study demonstrates ERT’s ability to identify critical subsurface features, with low resistivity zones indicating water-saturated areas and high resistivity zones marking air-filled voids. Time-lapse ERT imaging successfully captured dynamic resistivity shifts, correlating with key processes like soil displacement around burrows. Despite potential limitations, such as environmental noise and the influence of synthetic road plates used as protective coverings, ERT proved effective in detecting internal erosion patterns and pre-existing structural weaknesses. The results indicate that ERT offers a feasible, scalable approach, also for real-time levee monitoring in overflow scenarios, enhancing its applicability for validation of erosion models. Future studies should investigate the effect of cumulative damage during overflow testing and optimize forms of data presentation to improve interpretability, ultimately refining ERT’s potential as a reliable tool for predicting levee vulnerabilities.